The New Criterion on Performance-Based Design and Application to Recent Earthquake Codes - Kasimzade, Azer A.; Nematli, Emin; Kuruoglu, Mehmet (Techno-press, 2023)
Performance-based design (PBD) is based on designing a structure with choosing a performance target under design criteria to increase the structure's resistance against earthquake effect. The plastic hinge formation is determined as one of the fundamental data in finite elements nonlinear analysis to distinguish the condition of the structure where more significant potential damage could occur. If the number of plastic hinges in the structure is increased, the total horizontal load capability of the structure is increased, also. Theoretically, when the number of plastic hinges of the plane frame structure reaches "the degree of hyperstaticity plus one", the structure will reach the capability of the largest ultimate horizontal load. As the number of plastic hinges to be formed in the structure increases towards the theoretical plastic hinge number (TPHN), the total horizontal load capability of the structure increases, proportionally. In the previous studies of the authors, the features of examining the new performance criteria were revealed and it was formulated as follows "Increase the total number of plastic hinges to be formed in the structure to the number of theoretical plastic hinges as much as possible and keep the structure below its targeted performance with related codes". With this new performance criterion, it has been shown that the total lateral load capability of the building is higher than the total lateral load capability obtained with the traditional PBD method by the FEMA 440 and FEMA 356 design guides. In this study, PBD analysis results of structures with frame carrier systems are presented in the light of the Turkey Building Earthquake Code 2019. As a result of this study, it has been shown that the load capability of the structure in the examples of structures with frame carrier system increases by using this new performance criterion presented, compared to the results of the examination with the traditional PBD method in TBEC 2019.
Kasimzade, Azer/0000-0002-2487-3813; Nematli̇, Emin/0000-0002-1418-5654
Keywords: Finite Element Method; Load Bearing Capacity; Performance-Based Design (PBD); Plastic Hinge; Pushover Analysis